Integrated Management of Human-Elephant Conflict-A Success Story Involving Surgical Intervention on a Wild Elephant - Mohan, Justin J.; Kumar, Praveen S. (Indian Forester, 2023)
Human-elephant conflict has emerged as a significant wildlife management issue in Kerala and other parts of the country, causing loss to human life and property. While straying of elephants from their natural habitat into adjoining villages could be due to variety of reasons, forest administrators should identify the cause of the problem and address the same instead of being carried away by public opinion on handling the issue. Elephants are generally shy animals which avoid conflict with humans unless compelled to do so. The officials of the Forest Department face a variety of human-elephant conflict and each experience becomes a learning opportunity to handle the next conflict in a better way. The present study elaborates on how a hapless injured elephant which strayed into a village for feed was managed, by restraining and treating the animal and giving it a new lease of life. It also highlights the importance of an integrated approach while handling human-elephant conflict adopting a combination of practices that could result in a win-win situation for the animal and the affected people. This involves training an expert group of officials who would form a strategic human resource who can manage crisis situations to prevent loss of life and property due to human elephant conflict.